1987
DOI: 10.1002/jsfa.2740380307
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment of defatted oil meals of melon (Colocynthis citrullus L.) and fluted pumpkin (Telfaria occidentalis hook) by chick assay

Abstract: A B S T R A C TAnalytical data on fatty acid, amino acid and mineral content of defatted melon seed and fluted pumpkin seed are presented and discussed. Also discussed are experimental data on availability of amino acids and minerals in these meals. Defatted melon seed and fluted pumpkin seed have protein contents of 66.20% and 66.54%, respectively, with an excellent pattern of amino acids, containing higher levels of most essential amino acids (except lysine) than soya bean meal. Amino acid avaiiability is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 7 publications
0
29
2
1
Order By: Relevance
“…After oil extraction the content of protein increases reaching over 70% of dry matter in cake [23]. The experiments of Nwokolo and Sim [18] showed that pumpkin protein was similar to soybean cake in high availability of amino acids. Information on chemical composition and nutritional value of products obtained after pressing and/or extracting oil from pumpkin seeds is still fragmentary.…”
Section: Introductionmentioning
confidence: 94%
“…After oil extraction the content of protein increases reaching over 70% of dry matter in cake [23]. The experiments of Nwokolo and Sim [18] showed that pumpkin protein was similar to soybean cake in high availability of amino acids. Information on chemical composition and nutritional value of products obtained after pressing and/or extracting oil from pumpkin seeds is still fragmentary.…”
Section: Introductionmentioning
confidence: 94%
“…After the extraction of oil from the ground seeds (Cucurbita moschata) the residual cake contains about 730 g kg-l crude protein (Sharma et al 1986). In West Africa, especially in Nigeria, pumpkin seeds are served, cooked and dried, as snacks; the seed may also be cooked, ground and fermented for use as a flavour enhancer in gravies and soups (Nwokolo and Sim 1987). In Egypt the pumpkin seed is eaten as a nut.…”
Section: Introductionmentioning
confidence: 99%
“…Pumpkin seed oil are good source of vitamins, minerals and anti-oxidants [37], it has many therapeutic activities like antioxidant activity [42] [44], anti inflammatory [45], antimicrobial activity [46] [47], and anti carcinogenic effect [48].…”
Section: Discussionmentioning
confidence: 99%
“…Pumpkin seed oils are good source of vitamins, minerals and anti-oxidants [37]. Active components include fatty acid, 19.4% saturated fatty acids (palmitic K. E. Sharquie et al acid and stearic acid), 80.7% unsaturated fatty acids (linoleic acid and oleic acid) [38], Tocopherol (β-tocopherol, γ-tocopherol, δ-tocopherol), carotenoids including β-carotene and lutein [39], Phytosterols or plant sterols [40], Amino acid Glutamic and aspartic acid, leucine, valine, phenylalanine, and tryptophan are among the amino acids identified [41].…”
Section: Introductionmentioning
confidence: 99%